A new species of Stichorkis (Orchidaceae, Malaxidinae) from Sarawak in Malaysia - Margońska, Hanna (Biodiversity: Research and Conservation, 2010)
A new species Stichorkis mieczyslawiana is described and illustrated. A brief explanation of the status and characteristics of genus Stichorkis are given.